Financial cycles in asset markets and regions - John Beirne (Asian Development Bank Institute (ADBI), 2019)
This paper provides a comprehensive analysis of financial cycles in asset markets and regions. Using a large sample of 38 advanced and emerging economies to enable a comparative assessment, the analysis conforms with the prevailing literature on financial cycles pertaining to advanced economies, but finds that equity market cycles in emerging market economies in Asia, Latin America, and Eastern Europe may be a more useful gauge of the financial cycle compared to cycles in credit and property markets. Similar to more advanced economies, it is found that financial and business cycles in emerging economies are synchronized, albeit partially and with some cross-country heterogeneity. This underscores the importance for policy makers to be vigilant of interlinkages between real and financial sectors, pointing toward a need for carefully designed macroprudential policies. Finally, it is found that financial cycles in emerging markets remain vulnerable to global risk aversion in financial markets and spillovers from the United States, thereby reinforcing the importance of continuing to strengthen domestic macroeconomic fundamentals, and develop further local financial sectors through targeted structural reforms.
Keywords: C38; E32; E44; 330; financial cycle; business cycle; emerging markets